2000
DOI: 10.1063/1.1311946
|View full text |Cite
|
Sign up to set email alerts
|

Capacitance and admittance spectroscopy analysis of hydrogen-degraded Pt/(Ba, Sr)TiO3/Pt thin-film capacitors

Abstract: One of the problems occurring in conjunction with the integration of Ba 0.7 Sr 0.3 TiO 3 ͑BST͒ thin film capacitors into the Si technology is the large increase of leakage current after a forming gas heat treatment. In order to reveal the underlying mechanism, we studied the electric properties of Pt/ BST/Pt ͑metal-insulator-metal͒ ͑MIM͒ structures after annealing in atmospheres containing hydrogen (H 2 ) or carbon monoxide by means of admittance spectroscopy. Frequency-dependent capacitance measurements on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…On the low-frequency (<100 kHz) side, the ac conductivity increases with temperature, and it shows little frequency dependence. At high frequencies, the dielectric behavior is related to the short range hopping of charge carriers through trap sites separated by barriers, while the behavior at a low-frequency plateau is attributed to dc conductivity generated by Schottky emission from the metal oxide-metal junction [19][20][21][22]. Two slopes can be drawn, one in the high frequency region above 100kHz and the other in the lower frequency region.…”
Section: Resultsmentioning
confidence: 97%
“…On the low-frequency (<100 kHz) side, the ac conductivity increases with temperature, and it shows little frequency dependence. At high frequencies, the dielectric behavior is related to the short range hopping of charge carriers through trap sites separated by barriers, while the behavior at a low-frequency plateau is attributed to dc conductivity generated by Schottky emission from the metal oxide-metal junction [19][20][21][22]. Two slopes can be drawn, one in the high frequency region above 100kHz and the other in the lower frequency region.…”
Section: Resultsmentioning
confidence: 97%
“…10,17 For the similar experiments of Pt/(Ba, Sr)TiO 3 /Pt thin film, it was reported that the activation energy determined by a low-frequency ac measurement agreed well with the 0 Schottky barrier heights by a dc measurement. 9 For Pt/ SBN/Pt junction, characteristics of electrical conduction were previously reported by I -V analysis, and conduction mechanisms were explained by the Schottky emission. Then the barrier height for conduction process was estimated to be 0.9 eV by Watanabe et al 10 and 1.0-1.2 eV by Seong et al 17 from the slope of leakage current density J vs 1/T plot.…”
mentioning
confidence: 99%
“…8,9 It is well known that the electrical properties of the SBT, (Ba, Sr)TiO 3 (BST), and Pb(Zr, Ti)O 3 ͑PZT͒ thin films on electrodes strongly depend on the state of the surface, and impurities or defects may act as traps or donors. [10][11][12][13] Waser et al suggested that the oxygen vacancy plays an important role in the resistance degradation and dielectric degradation of thin polycrystalline (Ba, Sr)TiO 3 films.…”
mentioning
confidence: 99%
“…Not only BST itself but also the electrode material for the BST film has been extensively studied since the properties of BST films such as the dielectric constant and leakage current density are strongly affected by the bottom electrode [4][5][6]. In this work, we propose a (Ba, Sr)RuO 3 [BSR] oxide electrode which has an outstanding structural match with BST and which is chemically compatible with BST.…”
Section: Introductionmentioning
confidence: 98%